Neoichnology of endolithic lichens: an update on the traces produced in fossil bones and teeth - Acosta Hospitaleche, Carolina Ileana Alicia; García, Renato Andrés; Pérez, Leandro Martín; Marquez, Gonzalo Javier (Historical Biology)
The present contribution is motivated by the frequent occurrence of traces generated by lichens on the fossil record, the usual and erroneous attribution of them to plant roots, and the scarce information published about bioerosive damage caused by lichens. As a result, two different patterns were identified on the surface and inside the fossil bones and teeth. The first one is characterised by the presence of lines clearer than the rest of the surface, produced by the hyphae and interrupted by small pits corresponding to the apothecia. These traces are often confused with Corrossichnia and Sphenoichnia, a situation that leads to taphonomic and palaeoecological misinterpretation. The second pattern, more unnoticed among other visible traces, consists of isolated pits without any other surficial trace distributed in the fossil surface. These pits can be confused with perforations made by many organisms. However, the presence of apothecia and, in some cases, also hyphae on the fossil remains, allows the accurate identification of the causal agent and the mechanism of action by which it occurs. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: García, Renato Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Avellaneda; Argentina Fil: Pérez, Leandro Martín. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleozoología Invertebrados; Argentina Fil: Marquez, Gonzalo Javier. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Área Paleobotánica; Argentina